Antibacterial Effect of Alcoholic Extract of Juglans regia L. stem bark and Inner Stratum of Oak Fruit (Jaft) on Staphylococcus aureus isolated from wound infection - Sarwa Azeez Khalid; Nihad A. Jaafar (Tikrit Journal of Pure Science)
Staphylococcus aureus can cause a wide spectrum of infections ranging from wound infections to life threatening systemic illnesses. These bacteria have multi drug resistance and can be difficult to treat. This study included a total of 20 Staphylococcus aureus isolated from wound infection, identification of Staphylococcus aureus  was based on growth on manitol salt agar, DNase test, coagulase test. Alcoholic extract of inner stratum of Oak (Jaft) and stem bark of Juglans regia L. were tested for the activity against this bacterium by determination the Minimum Inhibitbitory Concentration (MIC). The results showed that both Jaft and Juglans regia L. stem bark  extract have effect against Staphylococcus aureus ,the values of MIC of Jaft extract against isolates ranged between o.39 -12.5mg/ml with average of 3.9 mg/ml, and the values of MIC of Juglans regia L. stem bark ranged between 0.39-12.5mg/ml with average  of 6.3 mg/ml.